2023
DOI: 10.1007/s13304-023-01560-1
|View full text |Cite
|
Sign up to set email alerts
|

New techniques versus standard mapping for sentinel lymph node biopsy in breast cancer: a systematic review and meta-analysis

Abstract: New tracers for sentinel lymph node biopsy (SLNB), as indocyanine green (ICG), superparamagnetic iron oxide (SPIO) and micro bubbles, have been recently introduced in clinical practice showing promising but variable results. We reviewed the available evidence comparing these new techniques with the standard tracers to evaluate their safety. To identify all available studies, a systematic search was performed in all electronic databases. Data regarding sample size, mean number of SLN harvested for patient, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…However, if the SN exhibits metastasis, applying the results of the American College of Surgeons Oncology Group Z0011 (ACOSOG Z0011) trial, which showed no difference in 10-year survival between omitting and adding axillary dissection when only a few metastases were detected after sentinel node biopsy in patients with invasive breast cancer (cT1-2 and cN0), to the second SNB is debatable [ 23 ] and requires further confirmatory studies. Although the newer methods of SNB, such as ICG, SPIO, and CEUS, have been reported and compared with conventional methods [ 24 26 ], there are no reports available on their use in a second SNB. In the case of IBTR, conducting a study under uniform conditions remains difficult, given the wide variations in the location and size of the wound and postoperative treatment, such as radiotherapy and adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the SN exhibits metastasis, applying the results of the American College of Surgeons Oncology Group Z0011 (ACOSOG Z0011) trial, which showed no difference in 10-year survival between omitting and adding axillary dissection when only a few metastases were detected after sentinel node biopsy in patients with invasive breast cancer (cT1-2 and cN0), to the second SNB is debatable [ 23 ] and requires further confirmatory studies. Although the newer methods of SNB, such as ICG, SPIO, and CEUS, have been reported and compared with conventional methods [ 24 26 ], there are no reports available on their use in a second SNB. In the case of IBTR, conducting a study under uniform conditions remains difficult, given the wide variations in the location and size of the wound and postoperative treatment, such as radiotherapy and adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the comparison between ICG and the standard dual RI + BD technique, two meta-analyses concluded that ICG alone is comparable as a tracer with the standard dual mapping [66,67]. Furthermore, ICG was reported to be even better than the traditional dual RI + BD method by two other meta-analyses studies regarding the SLN's identification rates [63,65]. Finally, the combined ICG + BD method, as well as the combined ICG + RI method, can both be used as effective mapping methods, alternative to the standard dual RI + BD technique [68,69].…”
Section: Meta-analyses On the Use Of Icg As Slnb Tracer For Breast Ca...mentioning
confidence: 99%
“…Kedrzycki et al and Thongvitokomarn et al, in their meta-analyses that included 944 and 4216 patients, respectively, concluded that ICG is equivalent to RI and superior to BD regarding the SLN identification rates [63,64]. Rocco et al and Yin et al, in their meta-analyses that included 3980 and 2671 patients, respectively, reported that ICG is a significantly better tracer compared with conventional single tracers (RI alone or BD alone) [65,66]. Regarding the comparison between ICG and the standard dual RI + BD technique, two meta-analyses concluded that ICG alone is comparable as a tracer with the standard dual mapping [66,67].…”
Section: Meta-analyses On the Use Of Icg As Slnb Tracer For Breast Ca...mentioning
confidence: 99%
“…As a result of this study, Martelli et al wished to evaluate the outcomes in this setting of patients. They assessed OS and DFS in the case of SLNB alone in cN0 patients (81) versus SLNB + ALND in cN1 patients (272) and, during a 10-year follow-up, OS and DFS of the SLNB-alone group presented no statistical differences compared to the SLNB + ALND group, with no axillary recurrences in the SLNB-alone group [48].…”
Section: Effect On Outcomementioning
confidence: 99%
“…However, some issues related to this context (i.e., high costs, few centers with nuclear medicine facilities, potential allergic reactions to the tracer, etc.) have required new tracers to be studied, such as indocyanine green (ICG), superparamagnetic iron oxide (SPIO), and carbon nanoparticles (CNPs) [79][80][81][82].…”
Section: State Of the Art Of Sln Mapping Techniques In Patients Subje...mentioning
confidence: 99%